The Role of Monitoring and Evaluation of Teacher Performance Systems in Elementary Schools to Improve School Quality - Agustina, Agustina; Pujiati, Sri; Elfrianto, Elfrianto (Indonesian Journal Education, 2023)
This study discusses the importance of implementing a system for monitoring and evaluating teacher performance in elementary schools as an effort to enhance the quality of education. This approach enables schools to regularly monitor and evaluate teacher performance, identify areas in need of improvement, and provide appropriate support to teachers. Challenges in measuring and enhancing teacher performance include differences in educational backgrounds, limited resource availability, and evolving curriculum demands. However, through the monitoring and evaluation system, schools can address these challenges by conducting regular data collection, data analysis, and development of relevant strategies. The benefits of implementing this system include improved quality of teaching and learning in classrooms, teacher performance enhancement, increased student achievement, more effective resource management, enhanced school accountability, and the development of a sustainable learning culture. Recommendations for implementing this system include establishing adequate infrastructure, providing training for school staff, fostering a culture of continuous learning, involving all stakeholders, and using findings from data analysis to design relevant professional development programs. It is hoped that the implementation of the teacher performance monitoring and evaluation system will become more effective in enhancing the quality of education in elementary schoolsThis study discusses the importance of implementing a system for monitoring and evaluating teacher performance in elementary schools as an effort to enhance the quality of education. This approach enables schools to regularly monitor and evaluate teacher performance, identify areas in need of improvement, and provide appropriate support to teachers. Challenges in measuring and enhancing teacher performance include differences in educational backgrounds, limited resource availability, and evolving curriculum demands. However, through the monitoring and evaluation system, schools can address these challenges by conducting regular data collection, data analysis, and development of relevant strategies. The benefits of implementing this system include improved quality of teaching and learning in classrooms, teacher performance enhancement, increased student achievement, more effective resource management, enhanced school accountability, and the development of a sustainable learning culture. Recommendations for implementing this system include establishing adequate infrastructure, providing training for school staff, fostering a culture of continuous learning, involving all stakeholders, and using findings from data analysis to design relevant professional development programs. It is hoped that the implementation of the teacher performance monitoring and evaluation system will become more effective in enhancing the quality of education in elementary schools